Plauti per uestigia, la auctoritas plautina en la comedia latina medieval: los ejemplos del anónimo Querolus siue Aulularia y de la Aulularia de Vital de Blois - Molina Sánchez, Manuel (Cuadernos de Filología Clásica. Estudios Latinos, 2007)
Despite the fact that a large number of his comedies have been lost, and admitting his relative lack of fame in the Middle Ages, Plautus’ auctoritas was still recognized during this age, either explicitly, as in the case of the Querolus, or as a literary ’memory’, for practical purposes restricted to the use of his name, as in the Aulularia by Vitalis Blesensis. The influence of the writer born in Sarsina to be seen in these works is different in degree: whereas the author of the Querolus professes admiration for his Latin predecessor, Vitalis Blesensis, although he recognizes Plautus’ worth, feels himself clearly his superior. What the French cleric does not know, however, is that the author he criticizes is not Plautus himself, but the anonymous writer of the Querolus.